A rare case of tularemic meningitis in the United States from aerosolized Francisella tularensis. Issue 3 (10th April 2020) - Venkatesan, Sriram; Johnston, Christopher; Mehrizi, Masoud Zarezadeh
Abstract: Tularemia is a rare zoonotic disease caused by Francisella tularensis . It can often present with varied clinical presentations, but meningitis is extremely rare. In this case study, we describe a patient who presented to our emergency department with a Tularemic infection coupled with acute atypical meningitis, after he was exposed to aerosolized rabbit hair from lawn mowing. Prompt diagnosis of tularemic meningitis may be difficult without a known history of animal exposure. Despite what is taught in medical school, numerous studies have shown Kernig's sign, Brudzinski's sign, and nuchal rigidity do not have much diagnostic value in adults with meningitis. Yet, almost all patients with meningitis present with at least 2 of the 4 symptoms of fever, headache, altered mental status, and neck stiffness. For this reason, it is essential to stop using Kernig's sign and Brudzinski's sign as the only basis for diagnosing meningitis in every case. With the rampant population increase of rabbits in states like Colorado, Missouri, and Illinois, and a growing number of tularemic patients from lawn mowing incidents popping up across the country, it is also vital to consider the diagnosis of tularemia in your differential diagnosis and send for a cerebrospinal fluid culture, based on a more detailed historytaking of your patient, specifically noting his/her outdoor activities during the initial assessment in the emergency department (ED). This would immensely speed up the process of diagnosing the patient and would ensure a timely start of antibiotics for a full recovery.